Some Insight on the Death of Bamboo after Flowering - Garg, Ramesh K.; Sharma, Rajesh K.; Kothari, R. M. (Indian Forester, 1998)
After the vegetative growth from rhizomes for a period of 50-80 years, clumps of bamboo, D. strictus, in a particular area undergo flowering, setting free enormous quantities of seeds and die synchronmisly. Changes in major constituents of bamboo (Î±-cellulose, hemicellulose, reducing sugars, starch, lignin, moisture and ash) at different stages of the above process are monitored in the light of supporting evidence form literature, some light is thrown relating to bamboo death. It seems that bamboo death may have been caused by excessive deprivation of reducing sugars and moisture content, leading to loss in vitality and osmotic shock along with toxicity generated due to enormous increase in lignin content.